Dysfunction of Islamic Religious Education in the SDGs Era: Challenges in Internalizing Islamic Values for Youth Responsibility - Afdhal, Surya; Ritonga, Mahyudin; Nasution, Alex Jimmi; Eric Salonen (Universitas Muhammadiyah Surakarta, 2025)
Objective: This study aims to identify the causes of the failure to internalize Islamic values in mosque youth that cause a gap between ritual and social piety. The focus is on community factors that influence the social behavior of the young generation in the context of achieving the SDGs. Theoretical framework: The theoretical framework refers to the concepts of internalization of religious values, Islamic social piety, and experiential learning from the perspective of continuing education. This approach emphasizes the integration of spiritual and social dimensions in behavior formation. Literature review: Previous studies have shown the role of religious institutions in moral formation, but there is still a gap between religious practice and social behavior. The perspective of adolescents as the main subject of value internalization is still rarely studied. Methods: The research used a phenomenological qualitative approach with the location of the Al-Muzakkirin Mosque in Padang. Data were collected through observation, interviews, documentation, and FGDs, and then analyzed thematically by triangulation. Results: Five factors were found to cause failure, namely material dichotomy, ineffective lecture methods, exemplary inconsistencies, peer group pressure, and lack of social action. Adolescents experience a mismatch between religious knowledge and social practices. Implications: The findings encourage the development of contextual, participatory, and social experience-based mosque youth coaching. This model supports the implementation of continuing education and strengthening community partnerships. Novelty: Novelty lies in the exploration of adolescent perspectives that were often overlooked in previous studies. The research also produced an